Influence of carbonation on chloride penetration of pastes under cyclic wetting–drying conditions. Issue 3 (27th March 2021) - Chang, Honglei; Liu, Jian; Cheng, Sen; Zhang, Xuan
Abstract : Under a cyclic wetting–drying chloride attack environment, carbonation is of great significance for chloride transport. In this work the impact of carbonation on the chloride penetration rate was investigated by exposing normal cement paste specimens and pre-carbonated paste specimens with different water/binder ratios and mineral admixtures to the same cyclic wetting–drying conditions. It was found that either a denser pore structure or a higher chloride binding capacity can slow down chloride penetration. The chloride penetration rate thus depends on the combination of the pore structure, which determines the general permeability of cement pastes, and the chloride binding capacity. However, carbonation is more likely to accelerate chloride penetration regardless of the pore structure, due to the overwhelming decrease in the chloride binding capacity as a result of carbonation.